Green Building Materials for Circular Economy - Geopolymer Foams - Kinga Korniejenko,; Kinga Pławecka,; Patrycja Bazan,; Beata Figiela,; Barbara Kozub,; Katarzyna Mróz,; Michał Łach, (Proceedings of Engineering and Technology Innovation, 2023)
This study aims to design and investigate foamed geopolymers as a green material dedicated to the circular economy. For synthesis as raw material, the main waste materials of two Polish coal mines, Wieczorek and Staszic, are applied. Additionally, various foaming methods are employed to utilize the by-product of energy production, especially the fly ash generated by the Skawina power plant. In this study, the main issues addressed are related to the selection of the most appropriate foaming agent and the optimization of the process parameters, including temperature, time, and mixture components. Hydrogen peroxide, aluminum powder, and a commercial foaming agent are selected as foaming agents in this research. During the process of sample preparation, stabilizers are applied in the form of polyglycol and cellulose. Through the conducted test, the results show that hydrogen peroxide and aluminum powder emerged as the two most optimal foaming agents.